Dinamika Sosial dalam Pengelolaan Perpustakaan Sekolah: Studi Kasus di SMA Negeri 1 Deli Tua - Wizman, Wizman; Subhilhar, Subhilhar; Irmayani, Tengku (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2025)
This study aims to analyze the social dynamics (actor relations, power structures, and norms) in the management of school libraries and their impact on the implementation of the School Literacy Movement (Gerakan Literasi Sekolah/GLS) at SMA Negeri 1 Deli Tua. The research employs a qualitative approach with an intrinsic case study design. Data were collected through triangulation methods: participant observation, in-depth interviews (with the principal, head librarian, teachers, and students), and policy document analysis. Participants were selected using purposive sampling. Data analysis was guided by the framework of social practice theory. The findings reveal that social dynamics—particularly centralized power, role conflicts, and conservative norms—have created a disjuncture between national policy (Permendikbud No. 23/2015) and field-level practice. Transforming school libraries requires a restructuring of power relations, strengthening of human resource capacity, and the integration of context-based multiliteracies. The impact of the GLS implementation remains suboptimal, as evidenced by incidental literacy practices and digital transformation hindered by staff technophobia.